PENCEGAHAN TINDAK PIDANA PENCURIAN MELALUI PEMBINAAN DAN KONSELING PSIKOLOGI DI DESA PATUMBAK I KECAMATAN PATUMBAK - Maswandi Maswandi; Nanang Tomi Sitorus; Khairuddin Khairuddin; Raja Dewan Sanjaya; Najwa Aliya (LPPM Institut Pendidikan Nusantara Global, 2025)
Community Service in Patumbak-I Village, Patumbak District is a village located in Deli Serdang Regency which is not far from Medan City with a distance of 21.8 km for 47 minutes. Community Service is a follow-up to the collaboration that has been carried out between Medan Area University and the Patumbak-I Village Government. This activity was carried out by conducting legal socialization with the theme